Diagnostic performance of ultrasound in the assessment of parametrial involvement before surgery in cervical cancer patients (diagnostic accuracy study). (1st November 2019) - Fischerova, D; Ballaschova, T; Dostalek, L; Frühauf, F; Zikan, M; Slama, J; Kocian, R; Germanova, A; Němejcova, K; Jarkovsky, J; Cibula, D
Abstract : Introduction/Background: To evaluate the performance of 2-dimensional (2D) ultrasound in preoperative assessment of parametria involvement in patients with cervical cancer planned for primary surgical treatment. Histopathological findings from radical hysterectomy/trachelectomy/parametrectomy were used as a reference standard. Methodology: Patients with biopsy-proven cervical cancer evaluated on ultrasound and planned for primary surgery 01/2004 and 12/2017 were prospectivelly enrolled. The predefined protocol for ultrasound assessment included the presence of tumor, maximum tumor size, tumor-free distance (TFD), the parametrial involvement status, grade of parametrial infiltration and lymph node status. Results: Altogether, 722 patients were included, out of them 77 patients (11%) were excluded for tumor duplicity, absence of index test or reference standard. Data of 645 patients were analysed, 555 early stage cases (T1[except T1b3], T2a1, FIGO 2018) and 90 locally advanced stage (T1b3 and higher [except T2a1], FIGO 2018). The median age was 42 years and BMI was 24.5. Sixty-two patients (10%) underwent neoadjuvant chemotherapy (NACT). The maximum tumor size was 19.5 mm. The histologically confirmed prevalence of infiltrated parametria was 3.9% (25/645), with 12 cases correctly identified by the ultrasound. Ultrasound did not detect 11 cases (1.7%) with microscopic spread (<2 mm) and 2 cases (0.3%) with macroscopic infiltration (2.75 and 10.0 mm). The accuracy of ultrasound in parametrial detection reached 97% with diagnostic odds ratio 62.7. Conclusion: Ultrasound is very good method for preoperative assessment of parametrial involvement in cervical cancer with a minimal risk of failure to detect infiltration >2 mm. Disclosure: This work was supported by Charles University in Prague (UNCE 204065 and PROGRES Q28/LF1) and by a grant from the Czech Research Council (No 16-31643A). None of the authors declare any conflict of interest.